Prevalence and Predictors of Overweight and Obesity in Patients with Pituitary Dysfunctions - Harbeck, Birgit; Danneberg, Sven; Rahvar, Amir-Hossein; Monig, Heiner; S. Haas, Christian (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2016)
Background: Patients with hypothalamic-pituitary disorders (HPD) may be of increased risk to develop overweight and obesity, thereby fostering cardiovascular events. However, it remains unclear if patients with pituitary dysfunctions per se have an increased risk of becoming obese. Objective: The objective of this study was to evaluate prevalence and to identify possible predictors of overweight and obesity in patients with pituitary dysfunctions. Methods: A total of 121 out-patients having various causes for HPD were assessed for height and body weight; body mass index (BMI) was calculated and correlated with clinical features. Patients were divided into various subgroups depending on underlying conditions and therapeutic modalities. Results: Most of the HPD patients were overweight or obese with males being significantly more affected. Of interest, patients with macroadenomas suffered significantly more often from overweight and obesity than individuals with microadenomas (73.4% vs. 43.5%, p= 0.006). Increased BMI (≥25 kg/m2) tended to be more common in patients with prolactinomas (70.0%), hormone deficiencies (76.1%) and hormone replacement therapies (76.6%) than in a healthy population. Conclusion: In conclusion, we showed that patients with HPD: (i) frequently suffer from overweight and obesity; (ii) prevalence of overweight and obesity however is comparable to that in the general population; (iii) only patients with macroadenomas seem to have a significantly higher risk; (iv) hormone deficiencies and hormonal replacement therapy may foster weight gain and (v) radiation and surgical tumour therapy per se do not seem to be additional risk factors for weight gain.
Keywords: obesity